Thursday

March 26, 2015

March 26, 2015

Posted by **jen** on Friday, October 19, 2007 at 10:39pm.

Thanks so much xx

- maths -
**drwls**, Saturday, October 20, 2007 at 2:24amThe only solutions to 2r^2 - 3r -2 = 0 are

r = 2 and r = -1/2. You can prove that by factoring the equation.

The sequence a + ra + r^2 a + ...will not converge if r = 2. Therefore r must be -1/2.

Use the fact that the sum is 6 to figure out the first term, a

6 = a (1 -1/2 + 1/4 -1/8 + ...)

= a [1/(1 + (1/2))] = a*(2/3)

a = 9

**Answer this Question**

**Related Questions**

Maths - 1..The first 2 terms of a geometric progression are the same as the ...

Maths - Eric thinks of 2 sequences.One is geometric and the other arithmetic....

MATH - A new sequence is formed by adding together the corresponding terms of a ...

Math - A sequence is formed by adding together the corresponding terms of a ...

Math - first three terms of a geometric sequence are the same as the 1st, 9th ...

geometric sequence - The sum of the 2nd and 5th terms of a geometric sequence is...

Can someone help me?! - The 1st, 5th and 13th terms of an arithmetic sequence ...

math - if an is a geometric sequence where a1=4 and the sum of an=12. how would ...

Maths - The first, third and ninth terms of an arithmetic sequence form the ...

math - in an arithmetic sequence the common difference is equal to 2.the first ...